Morphophysiological performance of medium cycle soybean cultivars under flooding - Ludwig, Marcos Paulo; Oliveira, Sandro de; Schuch, Luis Osmar Braga; Vernetti Junior, Francisco Jesus; Seus, Rogério; Lemes, Elisa Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The increase in soybean cultivation in Brazil has reached areas previously used for other purposes, such as in regions of lowland soils, thus being subject to possible soil flooding. This study aimed to evaluate morphophysiological changes in medium cycle soybean cultivars, under soil flooding conditions, in the vegetative and reproductive stages to recommend cultivars. The experiments were conducted at the Estação Experimental de Terras Baixas, EMBRAPA Clima Temperado in the Capão do Leão city, RS. Three water management systems were applied: normal cultivation condition (without flooding), flooding in the vegetative stage (V3 / V4) and flooding during the reproductive stage (R2 / R3). During the crop cycle, plant height, diameter of the main stem, chlorophyll content index, phenology and number of nodes in the stem per plant were collected. On the basis of the results this study, it can be concluded that he flooding reduces the number of nodes on the main stem, reducing plant height, with the most pronounced effects when flooding occurs in the vegetative stage. Furthermore, flooding the reproductive stage promotes increased diameter of the main stem. Flooding causes delay of occurrence of phenological stages and the total cycle of soybean cultivars.